Unlocking the mysteries of n-oxPTH: implications for CKD patients - Zhang, Lina; Cao, Huixia (Frontiers in Endocrinology, 2025)
Parathyroid hormone (PTH) is a pivotal hormone that regulates serum calcium and phosphate and is closely associated with higher risk of cardiovascular disease and mortality in patients with chronic kidney disease (CKD). PTH can undergo oxidation at methionine 8 and methionine 18 of the molecule. This oxidation process leads to a lower binding affinity to the PTH receptor due to molecular refolding, particularly for PTH oxidized at methionine 8. Although, the oxidation of PTH has been reported for several decades, it is only recently that a method has been developed to detect non-oxidized PTH (n-oxPTH) levels. The utilization of this assay enables the precise detection of n-oxPTH levels and facilitates the evaluation of their correlation with poor prognosis in patients with CKD. However, the current available clinical research findings indicate that n-oxPTH does not demonstrate clinical superiority over iPTH. Here, we provide a comprehensive review on the mechanism of PTH oxidation, the n-oxPTH assay method, and its correlation with iPTH and clinical outcomes.